Redescription of the genus Arcilasisa Walker with notes on its taxonomic placement (Lepidoptera: Noctuidae: Noctuinae) - Chen, Enyong; Pan, Zhaohui; Volynkin, Anton V.; Saldaitis, Aidas (Zootaxa, 2022)
The poorly known monotypic noctuid genus Arcilasisa Walker, 1865 is redescribed. The hitherto unknown male and female genitalia of the type species of the genus, A. sobria Walker, 1865 are illustrated and diagnosed for the first time. The genus is placed in the Apamea Ochsenheimer, 1816 generic complex belonging to the subtribe Apameina Guenée of the tribe Apameini Guenée. The lectotype for the type species of the genus, Arcilasisa sobria Walker, 1865 is designated.